Morphometric Evaluation of Thoracic Vertebrae Using Multidetector Computed Tomography in Patients with Scoliosis - Nadire Ünver Doğan; Zeliha Fazlıoğulları; Ali Güleç; Mehmet Öztürk; Mehmet Cengiz Tatar; Ahmet Kağan Karabulut (Genel Tıp Dergisi)
Aims:Many people have congenital and acquired deformities associated with the vertebral column. Vertebral surgery is practiced in cases like scoliosis, traffic accidents, falling down from height, cancer, and disc hernia. We aimed to reduce morbidity and mortality by creating alternative predictions for surgery and treatment with the findings and results we obtained in our study in patients with scoliosis. Methods: Patients with scoliosis (eight male, eight female) who underwent thoracic vertebrae imaging by multidetector computed tomography at Selcuk University Faculty of Medicine between 2013 and 2017 and who were not operated and those without scoliosis (eight male and nine female) who underwent imaging for other reasons were retrospectively evaluated. The group aged >15 years was created in a similar way. Similarly, groups with thoracic X-ray and tomography were created; Cobb angles and the width, height, and distance between the dorsal tips of the transverse process were measured in the 12 thoracic vertebrae. Lateral distances from the midline junction of the right lamina of vertebra to the lateral of the right transverse process and pedicle of vertebra junction were measured; measurements were repeated for the left side and recorded. Measurements were made in 780 thoracic vertebrae. Results: Mean Cobb angle of 8 in 10–14-year-old male patients with thoracic scoliosis was 30.9° and mean age was 13 years. Mean Cobb angle of 8 in 10–14-year-old female patients with thoracic scoliosis was 32.72° and mean age was 12.75 years. Conclusion: Our results will be useful for manufacturers and surgeons in terms of producing personalized screws and plaques.